Prevention strategies against academic burnout: the perspective of Romanian health sciences students in the aftermath of the COVID-19 pandemic - Popa-Velea, Ovidiu; Stoian-Bǎlǎşoiu, Ioana Ruxandra; Mihai, Alexandra; Mihǎilescu, Alexandra Ioana; Diaconescu, Liliana Veronica (Frontiers in Psychology, 2025)
BackgroundBurnout in academia can have important long-term consequences. This study aimed to investigate academic burnout and the perception of its prevention strategies among Romanian health sciences students.MethodsThree hundred and five health sciences students (from General Medicine, Dental Medicine, Pharmacy, and Midwifery and Nursing) (36 men, 269 women, mean age 21.9, standard deviation 1.911) self-rated their burnout using the Burnout Assessment Tool (BAT) and a visual analog scale, and answered a survey with open and closed questions about the most effective coping strategies to prevent burnout.ResultsAbove average scores (mean = 3.05; SD = 0.67) on burnout were met (with the highest scores on exhaustion and psychological distress and the lowest on mental distance and psychosomatic symptoms). Women were more affected than men by burnout and associated emotional impairment and secondary symptoms. Participants rated supportive relationships as the most effective in preventing burnout (mean = 3.75; SD = 0.55), followed by relaxation-meditation (mean = 3.32; SD = 0.85), while they also positively valued cognitive-behavioral therapy (those with high burnout scores), and physical activity (those with low burnout scores). Organizational strategies have included re-evaluating the university curriculum (mean = 3.83; SD = 0.48) and increasing access to psychological support programs (mean = 3.72; SD = 0.58) and to programs that increase self-efficacy and resilience (mean = 3.65; SD = 0.61). The qualitative analysis showed that freely chosen individual strategies included, in descending order, detachment, active actions, healthy lifestyle, and specialist help, while the most preferred organizational were better academic organization and program optimization.ConclusionThese results may be useful in designing more sustainable and effective burnout prevention strategies in health sciences academic settings.